PEMANFAATAN CROWDFUNDING SEBAGAI SARANA PEMBIAYAAN BISNIS WARALABA - Dean Diyantha Putrandi; Satriawansyah Urbaya (ITB AAS Indonesia Surakarta, 2023)
Crowdfunding as a means of financing franchise businesses is becoming increasingly popular among entrepreneurs worldwide. Through crowdfunding, franchise owners can obtain the necessary funds to develop their business without relying on traditional sources of financing such as banks or investors. This research analyzes the use of crowdfunding as a source of financing for franchise businesses. The study is conducted using a qualitative descriptive method and data is obtained from literature review and interviews with several business owners who have successfully used crowdfunding to finance their franchise businesses. The results show that crowdfunding can be an effective alternative for obtaining funds for franchise businesses, especially for those who are just starting out or facing difficulties in obtaining financing from traditional financial institutions. However, the use of crowdfunding also comes with risks that need to be considered. One of the risks is the possibility of failing to reach the fundraising target. Therefore, franchise owners need to prepare thoroughly before using crowdfunding, such as creating a clear and attractive business plan for potential investors and conducting effective promotions to attract investor interest. In conclusion, the use of crowdfunding as a means of financing franchise businesses has great potential in supporting the development of franchise businesses. However, business owners need to consider the risks and prepare carefully before using crowdfunding in order to maximize the benefits of this source of financing.